Alterego - Lisa, 1997-; Montclare, Brandon (Zero Zero Entertainment, 2026)
"This 96 Page Graphic Novel is the official companion to the Alter Ego album, written by LISA and brought to vivid life by celebrated Japanese artist MINOMIYABI. Step into a neon-drenched cyberpunk city where Vixi -- a quiet tech genius -- prefers fixing arcade machines to seeking the spotlight. Despite her reserved nature, she becomes the unexpected bond that unites four remarkable friends: Roxi, a pressured social star yearning for genuine connection; Kiki, an unstoppable arcade champion with an unyielding spirit; Sunni, a gentle peacekeeper concealing her inner storms; and Speedi, a fearless risk-taker learning to slow down. When three ruthless bullies trap Vixi in a virtual reality nightmare, her friends dive headfirst into the digital battleground, proving that while Vixi may work alone, she never has to fight alone." -- Amazon.com.